Effect of Hydraulic Parameters on Cohesive Sediment Transport of Clay Soil - N. Sahoo,; M. Mahapatra,; D.Panigrahi, (Journal of Soil and Water Conservation, 2022)
The phenomenon of erosion of cohesive soil is much more complicated and less touched than that of soils. Hence, the research workers have attempted to control the important electrochemical variables and other related hydraulic parameters by conducting laboratory flume experiments.Various hydraulic parameters which are important in erosion of cohesive soil are not yet fully defined. As contrasted to sediments in which the weight and size of the particles are the principal sediment factors controlling erosion, hydraulic parameters like flow velocity, friction factor, tractive force, Reynolds number, Manning's roughness coefficient etc. are also some of the controlling factors of erosion of cohesive sediments. In the current research the effect of all these parameters were well studied on the erosion resistance of cohesive sediments. The salient findings were that cohesive sediment transport (CST) was found increasing logarithmically with flow velocity, increasing exponentially with both shear velocity and tractive force and decreasing exponentially with the friction factor.